Perancangan Website Pada La Terra Cafe Jambi Sebagai Media Promosi Dan Informasi - Syifa Munawarah Syifa Munawarah; Rezaldy Yuliagsa Darma; Teguh Anugrah; Dr. Dodo Zenal Abidin, S.Kom, M.Kom (Jurnal Informatika Dan Rekayasa Komputer(JAKAKOM), 2023)
The use of technology as a means of promotion and information, especially through websites, has become an important medium for conveying information. Likewise the promotion carried out by La Terra Café, although it has succeeded in utilizing social media as a promotional tool, La Terra Café does not yet have an official website that provides complete information about the Café. The purpose of website design is to make it easier to carry out promotions and convey information and improve marketing through more effective and efficient promotional media. This website is designed using the PHP programming language and MySQL database. The method used is the waterfall model, as well as the UML system model approach including use case diagrams, activity diagrams, and class diagrams. Through this research, it is hoped that La Terra Café can optimize the use of information technology in promoting their business.